On the robustness to corrosion in the life cycle assessment of an existing reinforced concrete bridge - Cavaco, Eduardo S.; Neves, Luis C.; Casas, Joan R. (Taylor & Francis, 2017)
Management of existing structures has traditionally been based on condition assessment, based on visual inspections, disregarding the susceptibility of different structural types to aging and deterioration. Robustness, as a measure of the effects of unpredictable damage to structural safety can be a complementary information to the results of inspection. Although robustness has mostly been used to evaluate the consequences of extreme events, a similar framework can be used to investigate the result of aging, allowing a better understanding of the potential effects of deterioration and allowing a better allocation of available maintenance funding. In this work, a probabilistic structural robustness indicator is used to quantify the susceptibility of structures to corrosion. The methodology is exemplified through a case study comprising an existing reinforced concrete bridge deck, heavily damaged due to reinforcement corrosion, and finally demolished due to safety concerns. Robustness measures the bridge deck safety tolerance to reinforcement corrosion. The principal effects of corrosion, including loss of area and bond between concrete and steel are modelled using a non-linear finite-element model, coupled with a Response Surface Method to compute the bridge reliability as a function of the corrosion level, and finally used to assess robustness. Results show that the redundancy of the bridge allows significant redistribution of loads between elements with different corrosion levels. As a result, the bridge presents significant robustness and tolerance to reinforcement corrosion.